Chapter Status of water quality and impact of dredging activities in four ports of the gulf of Aigues Mortes (France) - Chouba, Cyrine; Causse, Léa; Marie, Mylène; DELPOUX, Sophie; FREYDIER, Rémi; Toubiana, Mylene; MONFORT, Patrick; Pringault, Olivier; MONTIGNY, Chrystelle (Firenze University Press, 2023)
Marinas located at the land-sea interface, are both subject to autochthonous sources of pollution and form a receptacle for terrigenous inputs from upstream areas resulting in the qualitative degradation. The objective of this project is to carry out a diagnosis of the chemical and microbiological contamination of the waters of the 4 ports located in the Gulf of Aigues Mortes (France) concerning a mutualized dredging operation. The originality of the results lies in the fact that they will allow not only to compare the chemical and microbiological qualities of the waters of the marinas, but also to determine the impact of the same type of dredging on the resuspension of contaminants in the water column